Pengembangan Komik Digital sebagai Media Pembelajaran Bahasa Arab Maharah Qira’ah untuk Siswa Kelas X MA Almaarif Singosari - Meladia Aqidatul Izzah; Ali Ma’sum (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: The development of digital comic media is encouraged by creative and innovative learning media that have not been developed yet in learning Arabic of Almaarif Singosari Islamic Senior High School (MA). In addition, teachers have not maximized the use of technology as a learning medium. In the learning process the teacher still uses the media used in general, such as laptops, projectors, books, and blackboards. In qira’ah learning the teacher more often uses books from the ministry of religion and powerpoint as learning media. This research aims to develop a product of digital comics in Arabic as a medium for learning Arabic subjects regarding Maharah Qira'ah for grade X of Almaarif Singosari Islamic Senior High School (MA) students. After the product has been developed, it is then validated by material experts, media experts, teachers, and students to understand the feasibility of the digital comic media. The method used in this research was Research and Development using the ADDIE model. As for the results of validation by material experts, media experts, teachers, and students as a whole obtained a percentage 83,9%. From this percentage it can be concluded that digital comic media is stated to be very valid or suitable to use as a medium for learning Arabic related to Maharah Qira'ah for grade X of Islamic Senior High School (MA) students. Keywords: comic, Arabic, qira’ah, learning media Abstrak: Pengembangan media komik digital ini dilatarbelakangi oleh belum dikembangkannya media pembelajaran yang kreatif dan inovatif dalam pembelajaran bahasa Arab di MA Almaarif Singosari. Di samping itu, guru belum memaksimalkan penggunaan teknologi sebagai media pembelajaran. Dalam proses pembelajaran guru masih menggunakan media yang monoton, seperti laptop, proyektor, buku, dan papan tulis. Pada pembelajaran qira’ah guru lebih sering menggunakan buku dari KEMENAG serta powerpoint sebagai media pembelajaran. Penelitian ini bertujuan untuk mengembangkan produk berupa komik digital berbahasa Arab sebagai media pembelajaran bahasa Arab untuk maharah qira’ah kelas X MA Almaarif Singosari. Setelah produk selesai dikembangkan, kemudian divalidasi oleh ahli materi, ahli media, guru, dan siswa untuk mengetahui kelayakan media komik digital. Metode yang digunakan dalam penelitian ini adalah Research and Development dengan menggunakan model pengembangan ADDIE. Adapun hasil validasi produk oleh ahli materi, ahli media, guru, dan siswa secara keseluruhan memperoleh persentase sebesar 83,9%. Dari persentase tersebut dapat disimpulkan bahwa produk komik digital berbahasa Arab dinyatakan sangat valid dan layak digunakan sebagai media pembelajaran bahasa Arab maharah qira’ah untuk siswa kelas X MA Almaarif Singosari. Kata kunci: komik, bahasa Arab, qira’ah, media pembelajaran